A Systematic Literature Review on the Application of Behavioral Counseling and Self-Management Techniques in Indonesia: Insights into Career Maturity Development - Muh. Nur Alamsyah; Nur Hidayah; Fitri Wahyuni; Andi Iqram Anas (Research in Education, Technology, and Multiculture, 2024)
Abstract: This study examines the effectiveness of self-management techniques in enhancing students' career maturity through a systematic literature review (SLR) methodology. The research involved identifying, selecting, and analyzing scholarly works, including journal articles, theses, dissertations, and other academic sources. Ten studies were reviewed, focusing on the application of self-management techniques in group and individual counseling across various educational levels, such as junior high school, high school, and higher education. The findings underscore the role of self-management techniques as a significant tool for fostering students' ability to plan and make informed career decisions. These techniques enable students to identify their strengths, establish realistic career goals, and acquire the necessary skills for successful career development. The analysis reveals that self-management techniques significantly contribute to career maturity by promoting self-awareness, effective goal-setting, and improved decision-making abilities. They address challenges such as low academic motivation, limited career awareness, and indecisiveness. Furthermore, the research highlights the influence of environmental factors, including the support of counselors, schools, and families, in maximizing the effectiveness of these interventions. The adaptability of self-management techniques across diverse educational contexts demonstrates their utility in guiding students through career-related challenges, providing them with a structured framework to enhance their career planning capabilities. In conclusion, self-management techniques offer a comprehensive approach to improving career maturity, equipping students with the skills and confidence to navigate their career trajectories. This study contributes to the body of literature in guidance and counseling by offering evidence-based insights into the benefits of self-management strategies. The findings underscore the importance of integrating these techniques into educational and counseling practices to prepare students for the demands of evolving career landscapes.     Keywords: self-management, career maturity, behavioral counseling, career development, systematic literature review.